Leg exercises with a serrated rubber ball and virgin coconut oil can increase the skin moisture of the feet of Diabetes Mellitus patients - I Wayan Sukawana; Ni Made Wedri; Ni Komang Ayu Indriyani; I Made Sukarja (KHD-Production, 2025)
Chronic hyperglycemia in patients with Diabetes Mellitus can cause autonomic neuropathy, resulting in decreased skin moisture in the feet. This study aims to test the impact of foot exercises with a serrated rubber ball and Virgin Coconut Oil (VCO) on skin moisture in patients with Diabetes Mellitus. This study was a pre-experimental design with a sample of 19 respondents of type 2 Diabetes Mellitus patients, who were taken randomly. Skin moisture data for the feet were measured using a digital skin tester one day before and after treatment. Foot exercises with a serrated rubber ball and VCO were carried out every two days for 30 minutes within 3 weeks. The average skin moisture of the feet before treatment was 17.80% ± 3.62%, and after treatment, 26.46 ± 6.34%%. The results of the Paired Sample T-Test showed a significant effect of the combination of foot exercises with a serrated rubber ball and VCO on increasing the skin moisture of the feet of patients with Diabetes Mellitus (p-value = 0.00). Thus, applying foot exercises with a serrated rubber ball and VCO effectively increases the skin moisture of the feet of patients with Diabetes Mellitus.